0500 Skin Sympathetic Nerve Activity In Patients With Sleep Disordered Breathing. (27th April 2018) - Wang, D; Tang, Y; Kumar, A; Wong, J; Wright, K; Mitscher, G; Nava, L; Adams, D; Everett, T; Chen, P; Manchanda, S
Abstract: Introduction: Sleep disordered breathing (SDB) is associated with an increased risk of cardiovascular (CV) disease and stroke. Increased sympathetic tone may play a role in the pathogenesis of CV diseases. However, direct sympathetic nerve recording in patients with SDB is difficult to perform using the classical microneurography techniques. We have recently shown that skin sympathetic nerve activity (SKNA) recorded by standard ECG patch electrodes can be used to determine sympathetic tone in humans.Objective:To test the hypothesis that patients with SDB have increased sympathetic tone during sleep. Methods: Surface ECG Lead I (sampling rate 10, 000/s) and 12 channel polysomnography were recorded in 13 patients (ages 30 to 73 yrs, 1 male), including 10 with SDB and 3 without SDB. The signals were bandpass filtered 0.5–150 Hz to display ECG and 500–1000 Hz to display SKNA. We analyzed the average SKNA (aSKNA) and average heart rate (HR) for the whole recording period (475.56 ± 35.81 mins), including the time of rapid eye movement (REM) stage. Results: The aSKNA (µV) in SDB patients were 0.74 ± 0.11, significantly (p=0.0412) higher than that in patients without SDB (0.58 ± 0.04). REM stage was observed in 9 patients (6 with SDB, 3 without SDB). The REM duration averaged 56.11 ± 31.4 mins. The aSKNA (µV) in REM sleep were 0.58 ± 0.11 in patients with SDB, which is significantly higher than that during non-REM sleep (0.55 ± 0.09, p=0.0477). The aSKNA (µV) in REM sleep in patients without SDB were 0.51 ± 0.08, compared with non-REM stage (0.49 ± 0.06, p=0.1847). The sinus rate correlated positively and significantly (p<0. 0001) with aSKNA in both SDB and non-SDB patients (average r: 0.45, 95% CI: 0.39–0.50). Conclusion: The aSKNA is higher in patients with SDB than without SDB, and during REM sleep than not during REM (NSEM) sleep. SKNA is a valid noninvasive measure of sympathetic tone in patients with SDB. Support (If Any):